2010
DOI: 10.1002/qua.22680
|View full text |Cite
|
Sign up to set email alerts
|

Diatom–diatom interactions: Building potential energy surfaces and effect of intramolecular vibrations

Abstract: An optimal procedure for obtaining spherically averaged potentials for the interaction between two linear centrosymmetric molecules (Koide and Kihara, Chem Phys 1974, 5, 34) is extended here for the calculation of the leading anisotropy term of the interaction. It is found that by computing the potential just at nine specific relative orientations of the monomers, the main anisotropy term of the spherical harmonic expansion can be calculated exactly provided that the expansion does not involve more than the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…The vdW-DF-optB86b result [Fig. 9 (b)] for the FM O 2 -O 2 dimer is closer to highest-accuracy quantum chemistry calculations available in the literature for the quintet state of the dimer, which predicts an interaction energy of ∼ 14 meV 34 . The better result may be due to the fact that the optB86b exchange is similar to the exchange employed in the newer vdW-DF-cx 35 , where the exchange functional is constructed to be more consistent with the underlying justification of vdW-DF based on adiabatic connection 17 .…”
Section: Resultssupporting
confidence: 73%
“…The vdW-DF-optB86b result [Fig. 9 (b)] for the FM O 2 -O 2 dimer is closer to highest-accuracy quantum chemistry calculations available in the literature for the quintet state of the dimer, which predicts an interaction energy of ∼ 14 meV 34 . The better result may be due to the fact that the optB86b exchange is similar to the exchange employed in the newer vdW-DF-cx 35 , where the exchange functional is constructed to be more consistent with the underlying justification of vdW-DF based on adiabatic connection 17 .…”
Section: Resultssupporting
confidence: 73%
“…In a sense it is a generalization of the four-term expansion mentioned before to a more accurate nine term representation. Later on, this analysis was extended for the calculation of other terms, 59 where it was demonstrated that 𝑉 202 and 𝑉 404 can be obtained with the same level of precision, in comparison with the isotropic one, starting from the KK conformations. This conclusion was based on a comparison with a very accurate representation of the quintet state, based on calculations at 65 different geometries and involving 29 radial terms 29 obtained from numerical integration over the angular coordinates.…”
Section: Geometries and Spherical Harmonic Expansion Of The Potential...mentioning
confidence: 99%
“…In these studies,[58][59] it was demonstrated that the expressions for the coefficients 𝑉 000 and 𝑉 202 from KK conformations, are those collected in the following equations:…”
mentioning
confidence: 99%
“…In the experiments considered here, all molecules must be in their ground vibrational state so that an improved model could consist in obtaining PESs averaged over the ground vibrational state of the monomers. Very recently, 60 vibrational averages of the isotropic ͑f 000 ͒ and the leading anisotropic ͑f 202 ͒ terms were obtained by means of RCCSD͑T͒ calculations of the quintet state for a set of different intramolecular distances ͑Gauss-Hermite quadrature points͒ as well as a reduced set of relative orientations. It was found that the vibrationally averaged terms are just about 1% more attractive ͑in the well region͒ than the rigid rotor counterparts while being slightly more repulsive at shorter range.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%